Provenance of British Computing. (Communications of the ACM, 2014)
Several letters to the editor are presented in response to articles in previous issues including "Tom Kilburn: A Tale of Five Computers," by David Anderson, published in the May 2014 issue, "Toward a Pedagogy of Ethical Practice," by Chuck Huff and Almut Furchert in the July 2014 issue, and "Responsible Programming," by Vinton G. Cerf in the July 2014 issue.